Emerging From the Shadows: Consequences of Position Disclosure in Corporate Bankruptcy - Chen, Kevin D. (The Accounting Review, 2026)
ABSTRACT I examine how mandatory position disclosure of claimholders’ economic interests affects Chapter 11 bankruptcy outcomes. Exploiting a regulation that increased disclosure by creditors and equityholders on certain committees, I find that position disclosure is associated with a decrease in the length of bankruptcy cases, especially the duration of negotiations between claimholders across classes. Further, I show that position disclosure is associated with lower post-bankruptcy recidivism. Contrary to the concerns expressed by critics, I find little evidence that position disclosure reduced claimholders’ participation in committees or decreased trading in the market for bankruptcy claims. My findings highlight the overall benefits of position disclosure in facilitating negotiations during bankruptcy. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: D82; G33: G34; K22; M40.